Straßenbenutzungsgebühren. Mittel der Stauminderung und Verkehrslenkung. - Kossak, Andreas (Deutscher Verkehrs-Verlag, 2004)
Die Erhebung von Gebühren für die Benutzung von Straßen ist ein traditionelles Mittel der Finanzierung des Baus, der qualifizierten Erhaltung und des Betriebs der betreffenden Verkehrswege. Bereits im Jahr 1920 brachte der amerikanische Ökonom Pigou Straßenbenutzungsgebühren explizit aber auch in Verbindung mit dem Verkehrsmanagement, vor allem mit der Reduzierung von Überlastungen der Infrastruktur; er führte den Begriff "Congestion Pricing" ein. difu

Traffic congestion cause a substantial economic damage in all industrialized countries; according to actual qualified studies the damage in Germany is of a similar amount as the overall internal costs for the road sector. Studies and first experiences worldwide come to the result and prove respectively, that performance / distance based road pricing is a highly efficient instrument of reducing congestion both in intercity and city traffic - in particular if the toll rates are varied by time and area. Over and above, the data obtained in context with the congestion charging are of great value for improving external and internal (fleet management) traffic management instruments. difu
Keywords: Verkehr; Straßenverkehr; Verkehrsablauf; Verkehrspreis; Gebühr; Untersuchung; Wirkungsanalyse; Straßenbenutzungsgebühr; Maut; Road-Pricing; Verkehrslenkung; Staureduktion; Verkehrsstau; Staukosten